2010
DOI: 10.1093/brain/awq264
|View full text |Cite
|
Sign up to set email alerts
|

Taking both sides: do unilateral anterior temporal lobe lesions disrupt semantic memory?

Abstract: The most selective disorder of central conceptual knowledge arises in semantic dementia, a degenerative condition associated with bilateral atrophy of the inferior and polar regions of the temporal lobes. Likewise, semantic impairment in both herpes simplex virus encephalitis and Alzheimer's disease is typically associated with bilateral, anterior temporal pathology. These findings suggest that conceptual representations are supported via an interconnected, bilateral, anterior temporal network and that it may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
90
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 40 publications
15
90
2
4
Order By: Relevance
“…On the other hand, LGG patients' deficits, although milder than HGG patients', are more pronounced immediately after surgical resection (Campanella et al, 2015), and some specific lesion locations tend to compensate minimally (Ius, Angelini, Thiebaut de Schotten, Madonnet & Duffau, 2011). Moreover, previous studies testing semantic memory in patients with unilateral lesions (Campanella, D'Agostini Skrap & Shallice,2010, Lambon Ralph et al, 2010 or bilateral lesions but more pronounced within one hemisphere (Lambon Ralph et al, 2001), reported prominent verbal output deficits and mild or normal receptive performance. In a computation model proposed to account for this phenomenon (Lambon Ralph et al, 2001), semantic knowledge is hypothesised to rely on a bilateral, distributed semantic system, with the left hemisphere semantic areas having privileged connections to the left-M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, LGG patients' deficits, although milder than HGG patients', are more pronounced immediately after surgical resection (Campanella et al, 2015), and some specific lesion locations tend to compensate minimally (Ius, Angelini, Thiebaut de Schotten, Madonnet & Duffau, 2011). Moreover, previous studies testing semantic memory in patients with unilateral lesions (Campanella, D'Agostini Skrap & Shallice,2010, Lambon Ralph et al, 2010 or bilateral lesions but more pronounced within one hemisphere (Lambon Ralph et al, 2001), reported prominent verbal output deficits and mild or normal receptive performance. In a computation model proposed to account for this phenomenon (Lambon Ralph et al, 2001), semantic knowledge is hypothesised to rely on a bilateral, distributed semantic system, with the left hemisphere semantic areas having privileged connections to the left-M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%
“…Patients with unilateral brain damage have been reported with impaired performance on tasks involving verbal production as in picture naming, but spared recognition abilities (Lambon Ralph, Cipolotti, Manes & Patterson, 2010;Lambon Ralph, Ehsan, Baker, & Rogers 2012;Drane et al, 2008). Moreover, patients with semantic dementia tend to show different types of impairment depending on the predominant laterality of the atrophy, with patients with more pronounced left atrophy showing disproportionate production impairment compared to comprehension, and patients with a more pronounced right atrophy showing a similar impairment in production and comprehension (Lambon Ralph, McClelland, Patterson, Galton & Hodges, 2001).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Two of these three studies (Viskontas et al, 2000;Voltzenlogel et al, 2006) considered the score obtained on the personal semantic section of the AMI, and the remaining study employed the external composite score (which includes not only semantic details, but also repetitions and other types of details) of the Autobiographical Interview (AI; Levine, Svoboda, Hay, Winocur, & Moscovitch, 2002) as a measure of 'semantic' memory. A study that examined the impact of unilateral temporal lobe damage on semantic memory in general showed that on expressive semantic tasks (i.e., naming, fluency), patients with left unilateral lesions obtained significantly lower scores relative to patients with right unilateral lesions (Ralph, Cipolotti, Manes, & Patterson, 2010). The between-group difference, however, was not significant on receptive semantic measures.…”
Section: Design Prospective Cross-sectionalmentioning
confidence: 98%
“…Contemporary research evidence about the location and organisation of semantic memory largely comes from studying adult neuropsychology patients, particularly those with semantic dementia (SD) who present with progressive loss of conceptual knowledge (e.g., Bozeat, Lambon Ralph, Patterson, Garrard, & Hodges, 2000;Lambon Ralph, Cipolotti, Manes, & Patterson, 2010;Lambon Ralph & Howard, 2000). This research suggests that semantic memory is represented bilaterally in anterior temporal lobe regions (Lambon Ralph, Sage, Jones, & Mayberry, 2010;Pobric, Jefferies, & Lambon Ralph, 2007).…”
Section: Down Syndromementioning
confidence: 99%